Crystal structures of BnSP-7 and BnSP-6, two Lys49-phospholipases A(2): quaternary structure and inhibition mechanism insights - Magro, A. J.; Soares, A. M.; Giglio, JR; Fontes, MRM (Elsevier B.V., 2003)
Phospholipases A(2) are components of Bothrops venoms responsible for disruption of cell membrane integrity via hydrolysis of its phospholipids. A class of PLA(2)-like proteins has been described which despite PLA(2) activity on artificial substrate, due to a D49K mutation, is still highly myonecrotic. This work reports the X-ray structure determination of two Lys49-PLA(2)s from Bothrops neuwiedi pauloensis (BnSP-7 and BnSP-6) and, for the first time, the comparison of eight dimeric Lys49-PLA2s. This comparison reveals that there are not just two (open and closed) but at least six different conformations. The binding of fatty acid observed in three recent Lys49-PLA(2) structures seems to be independent of their quaternary conformation. Cys29 polarization by Lys122 is not significant for BnSP-7 and BnSP-6 or other structures not bound by fatty acids. These structures may be in an active state when nothing is bound to them and the Lys122/Cys29 interactions are weak or absent. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: phospholipase A(2); myotoxin; crystal structure; bothropic venom; quaternary structure changes; lack of catalytic mechanism